22q11.2 Deletion: Surgical and Speech Outcomes of Patients With Velopharyngeal Insufficiency Treated With a Superiorly Based Pharyngeal Flap as the Primary Surgery. Issue 6 (September 2018) - Álvarez Carvajal, Drina C.; Palomares Aguilera, Mirta M.; Geldres Meneses, María B.; Bravo-Torres, Sofía; Giugliano Villarroel, Carlos
Abstract : Abstract: The most frequent palate diagnoses in patients with chromosome 22q11.2 deletion syndrome are a classic submucous cleft, occult, and velopharyngeal insufficiency without cleft, which generates alterations in speech that require surgery. Surgical protocols are controversial owing to syndrome characteristics that make their handling more complex. Pharyngeal flap pharyngoplasty is effective for this type of patient. The objective of this study is to examine the surgical management of velopharyngeal insufficiency in patients with chromosome 22 deletion, using a pharyngeal flap as the primary surgery. The clinical records of patients with chromosome 22 deletion and velopharyngeal insufficiency between 2015 and 2017 were analyzed retrospectively. Eight patients underwent pharyngeal flap pharyngoplasty as a primary surgery, including 1 with velopharyngeal insufficiency without a cleft, 1 with a classic submucous cleft, and 6 with occult submucous cleft. The pre- and postoperative protocol performed by speech therapists and surgeons included clinical evaluation of the oral cavity; perceptual, video recording, and nasometry speech evaluation; and videonasopharyngoscopy. All perceptual parameters and nasometry results significantly changed. Of the cases, 88% achieved a flap with the expected width and height and complete closure of the velopharyngeal sphincter. One patient required flap revision. Four of the 8 patients achieved normal resonance, and 2 of 8 showed mild hypernasality. Using the pharyngeal flap pharyngoplasty as a primary technique to correct velopharyngeal insufficiency in patients with chromosome 22 deletion provides satisfactory outcomes and decreases the number of surgeries. Preoperative planning must be conducted carefully and needs to be individualized to be successful.